Therapeutic Management of Canine Dirofilariasis in Nagaland, India - Kuotsu, Keneisezo; Ozukum, Sashitola; Kuotsu, Neithono; Devi, N Bhumapati; Laltlankimi; Chutia, Tukheswar; Biswas, Newton; Das, Gunjan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Dirofilariasis is one of the most clinically important diseases in dogs. It is also called as heart-worm disease, which is a non-contagious parasitic disease caused by filarial or small thread-like worms, Dirofilaria immitis, and D. repens of the family Onchocercidae (Nelson et al., 2014; Adebayo et al., 2022). It is an arthropod-borne disease. The mosquitoes belonging to the genera Culex, Aedes, Anopheles, and Mansonia are principally responsible for the transmission of this disease (Borthakur et al., 2016). Transmission of the parasite occurs when a potential vector bites dogs during a blood meal. It takes about 6-7 months for the third-stage larvae (L3) to become adult parasites after entering the blood vessels of the hosts (Koutsu et al., 2022). After maturation, the adult worms reproduce and produce microfilariae (pre-L1), which are released in the host blood vessels and taken up by a feeding mosquito (Thilakarathne et al., 2023), and completed the lifecycle of the parasite.